System for Electronic Goods Sales in credit at PT. ADITECH By Using Visual Basic 6.0 - Santi Santi (Jurnal Manajemen Informatika, 2010)
PT.ADITECH is a company engaged in the sale of equipment - electronic equipment atdesignated for individuals. Payment methods on this company is divided into two ways, withmaturities and credit or cash payment.By using the existing sales process and then translate into the new system, with the aim tofurther the sales process is expected to increase.Penjabarannya can be seen from the DFD which consist of context diagram and diagram Zero,ERD and Normalization, and component - component of data processing such as consumergoods. By limiting the problem only on credit sales process, then created a simple program thatuses Visual Basic 6.0 programming language that writers ask for help processing the data - thedata above.